Altered fibrin clot structure in patients with atrial fibrillation and worsening renal function - Lau, Yee Cheng; Hardy, Lewis J.; Philippou, Helen; Blann, Andrew D.; Lip, Gregory Y. H. (Thrombosis and Haemostasis, 2016)
Note: The review process for this manuscript was fully handled by Christian Weber, Editor in Chief.